Analysis of Thermal Energy Conversion into Electric Power Inside a Porous Media Burner - Henriquez-Vargas, L; Bubnovich, V (2012)
A system for converting combustion heat into electric power is proposed on the basis of gas combustion in a thermoelectric porous element. A lean gas mixture is introduced into the porous medium, where the gas flow rate is changed at a regular interval of time and, as a result, the combustion front is confined within a specific region of the porous medium. A non-steady state temperature distribution was established along the flow direction, resulting in a steep and stable temperature gradient in the thermoelectric porous element. Numerical simulation showed that the total thermal efficiency increases when a leaner mixture is fed to the combustor, besides when the combustion wave propagation velocity increases the global thermal efficiency grows reaching values almost equal to the conversion efficiency of the thermoelectric element itself. Consequently, using the proposed system, the chemical energy can be effectively converted into electric power. © 2012 Pleiades Publishing, Ltd.